การเจาะดูดด้วยเข็มขนาดเล็กและตรวจเซลล์วิทยาในโรงพยาบาลพหลพลพยุหเสนา - Arunruviwat, Somchai (วารสารแพทย์เขต 4-5, 2018)
This is a retrospective study of FNAC. The aim of this study is to find out the incidence of FNAC and to determine the accuracy of FNAC of breast mass. The medical records were reviewed during October 2009 to September 2010. They were 765 cases and 841 cytologic reports with age between 7 to 88 years and average 42 years old. There were 89 males and 676 females. FNAC reports were as follows; benign 551 (65.52%), malignant 47 (5.59%), suggestive 133 (15.81%) and unsatisfactory 110 (11.88%). Breast was the most common organ of FNAC in 491 reports (58.38%) followed by thyroid 176 (20.93%) and neck 100 (11.89%). The cytologic reports were benign breast lesion 149 (17.72%), nodular goiter 105 (12.48%), fibroadenoma 66 (7.85%), and others respectively. FNAC of breast mass had sensitivity of 92%, specificity rate of 98%, accuracy rate of 96%, positive predictive value of 96%, negative predictive value of 96%, false positive rate of 4% and false negative rate of 8%.